Therapeutic significance and indications of pulmonary metastasectomy for hepatocellular carcinoma following liver resection. (December 2017) - Hu, Zhigang; Li, Wenbin; Huang, Pinbo; Zhou, Zhenyu; Xu, Junyao; Xu, Kang; Wang, Jie; Zhang, Heyun
Abstract: Background: To explore the therapeutic significance and indications of pulmonary metastasectomy (PMT) in hepatocellular carcinoma (HCC) patients with pulmonary metastasis (PM) following liver resection (LR). Patients and methods: PM-HCC patients who underwent LR were retrospectively enrolled, and survival outcomes and prognostic factors were analyzed. Patients were divided into PMT and non-PMT group, and propensity score matching (PSM) analysis was used for survival comparison. Prognostic analysis and survival comparisons were performed specifically in PMT patients. Results: Ninety-seven patients were enrolled, among which twenty-six underwent PMT while seventy-one did not. Survival outcome was superior in PMT group compared to non-PMT group (33.5 vs. 10.5 months) (p = 0.003), while no statistical difference was found after PSM analysis (33.5 vs. 11.2 months) (p = 0.138). Synchronous PM-HCC, serum alpha fetal protein≥400 ng/ml at PM diagnosis, no intrahepatic treatments (LR, ablation or transarterial chemoembolization) after LR, intrahepatic recurrence or metastasis at repeated PM diagnosis were inferior independent prognostic factors in PMT patients (p < 0.05). Superior survival outcomes were seen in candidate PMT patients when corresponding indications were satisfied (p = 0.014, p = 0.005). Conclusion: PMT might provide potential survival benefits in well selected PM-HCC patients who underwent LR. Well designed, multi-institutional studies with larger patient number were still to be required. Highlights: PM-HCC patients might acquire superior prognosis when intrahepatic tumors were controlled by LR. PMT might provide potential survival benefits in well selected PM-HCC patients. Synchronous PM-HCC, AFP≥400 ng/ml, no IHT after LR, IHRM when PM repeated were inferior independent prognostic factors. Well designed, multi-institutional studies with larger patient number were needed.